Wide range tuning of band gap energy of A3B2X9 perovskite-like halides. (June 2019) - Kim, Se-Yun; Yun, Yeonghun; Shin, Seunghak; Lee, Joon Hyung; Heo, Young-Woo; Lee, Sangwook
Abstract: We report the structural, optical, and electrical properties of A3 B2 X9 halides (where A = Cs, methylammonium (MA), formamidinium (FA), or ethylammonium; B = As, Sb, or Bi; X = Cl, Br, or I). Substitution results in tuning of lattice parameters involving crystal structure change, hence tuning of band gap energy, from 1.9 to 3.1 eV. Our results on the band gap energy, type, and crystal structure changes by A, B and X site substitution would give very useful information to develop wide band gap light-absorbers for diverse optoelectronic applications, including highly efficient and stable tandem solar cells. Graphical abstract: Unlabelled Image